Application of Project Based Learning Model to Increase Science Learning Achievement - Wisnu Mursabdo (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to determine whether there is any effect of the project based learning (PjBL) learning model on the learning achievement of 7th grade junior high school students in the field of science in the solar system. This study uses a quantitative approach by collecting 26 primary data on 7th grade students of Kanaan Christian Middle School Jakarta in the 2021/2022 academic year. The study was conducted from May to June 2022. The analysis used was parametric statistics using t-test to answer the hypothesis that there was a significant effect of the project based learning (PjBL) learning model on science learning achievement. The results of the analysis show that there is a significant effect of the project based learning (PjBL) learning model on science learning achievement, this is evidenced by the Sig value of 0.000 which is smaller than 0.05 and the t-value of 10.873. The conclusion of this study is the selection of the right PjBL learning model to be implemented in 7th grade science learning materials about the solar system.